Pengaruh Konsentrasi Garam dan Umur Telur Terhadap Tingkat Kesukaan Konsumen Telur Asin - Isti Rizky Latipah; Merry Muspita Dyah Utami; Joko Irsan Sanyoto (Politeknik Negeri Jember, 2017)
This research is an experimental experience that aims to know the effect of salt concentration and the age of the eggs on the level of consumer preferences towards salted eggs and to know the ideal level of salt concentration and the age of the eggs to get consumers preferred salted eggs. The research was done in Poultry Production Laboratorium of Politechnic of Jember from September 27th 2016 to October 25th 2016. The research design by Randomaized Complete Desaign (RCD) consisted of two factor. The first was salt concentration which contains 3 actions which are action of salt concentration 25% (A25), salt concentration 30% (A30) and salt concentration 35% (A30). The second, the age of the eggs contains 2 actions which are 3 days age (B3) and 14 days age (B14). There are 6 combination of action and each of action was redone 4 times so that able to gain 18 units of research. Preference research was directly done by taste the salted egg. People panelis for detect acceptance on this research is 30 people from workers and students of Politechnic of Jember and also citizens. The salt concentration 35% and 3 days egg age have significant effect toward consumer preferences on color and grity as the criteria, while salt concentrations and days egg age have no effect toward consumer prference on smell and taste of salted egg.